Enamel matrix derivative in the treatment of peri-implant diseases - a systematic review - Bompard, Xavier (2020)
Objective: To evaluate the benefit in terms of clinical, histological and radiographic outcomes of the adjunctive use of enamel matrix derivative (Emdogain® ; Straumann, Basel, Switzerland) on the non-surgical and surgical treatment of peri-implant diseases. Methods: A systematic literature search comprised three databases: PubMed, Scopus and Cochrane. Eligible studies were selected based on the inclusion criteria. Results: Seven studies were selected for data extraction. Two randomized clinical trials using Emdogain® as an adjuvant for non-surgical treatment of peri-implant mucositis; tree cohort studies and and two randomized clinical trials using Emdogain® as an adjuvant for surgical treatment of peri-implantitis. A reduction of the mean bleeding on probing (76.6%), probing depth (3.5mm), P. gingivalis counts and mean marginal bone level gain of 2,38±0.92mm was observed. Conclusions: Emdogain® has a positive effect on clinical and microbiological outcome of non-surgical treatment of peri-implant mucositis. Combined with grafting materials, it seems to improve bone fill after surgical treatment of peri-implantitis. More studies are necessary to determine the effects of Emdogain® alone in the clinical outcome of peri-implantitis treatment.